Nanostructures: Mussel‐Inspired Plasmonic Nanohybrids for Light Harvesting (Adv. Mater. 26/2014). (July 2014) - Lee, Minah; Kim, Jong Uk; Lee, Joon Seok; Lee, Byung Il; Shin, Jonghwa; Park, Chan Beum
<x xml:space="preserve">Abstract</x> The back cover image illustrates an innovative scheme for the fabrication of elaborate plasmonic core–shell nanohybrid architectures using multi‐purpose mussel‐inspired polydopamine nanolayers. The design flexibility and simplicity provides an effective way to develop plasmon‐enhanced solar‐energy‐conversion platforms. By coupling plasmonic resonators and photosensitizers on a sub‐nanometer scale through a simple solution‐based process, light absorption in photocatalytic systems can be greatly enhanced to boost artificial photosynthetic reactions, as shown by C. B. Park, J. Shin, and co‐workers on page 4463. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>